2008
DOI: 10.17221/661-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of garlic (Allium sativum L.) genetic resources collection - Information

Abstract: Maintenance of garlic (Allium sativum L.) genetic resources has had a long tradition in the Czech Republic. The collection was founded in 1951 and its current holder is the Crop Research Institute, Department of Vegetables and Special Crops in Olomouc. The collection consists of 613 genotypes. The oldest genotype was acquired in 1954. The collection has been evaluated according to the Descriptor list for Allium spp. (IPGRI 2001). 17 characters of the Descriptor list were supplemented with 5 additional characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 7 publications
2
23
0
2
Order By: Relevance
“…1996, Panthee et al. 2006, Stavělíková 2008). Now genetic characterization and mapping of garlic clones also has been accomplished using various molecular markers, such as isozymes (Pooler and Simon 1993, Cholakova 2000, Ipek et al.…”
Section: Number and Percentage (In Parenthesis) Of Accessions By Thementioning
confidence: 99%
“…1996, Panthee et al. 2006, Stavělíková 2008). Now genetic characterization and mapping of garlic clones also has been accomplished using various molecular markers, such as isozymes (Pooler and Simon 1993, Cholakova 2000, Ipek et al.…”
Section: Number and Percentage (In Parenthesis) Of Accessions By Thementioning
confidence: 99%
“…However, Khar et al (2011) and Senula and Keller (2000) reported that garlic exhibits a wide range of diversity in morphological, reproductive and bulb traits because of its apomictic nature which leads to the existence of extensive somatic mutations (Ata, 2005). It was further indicated by Jabbes et al (2012) that garlic presents, in spite of its vegetative multiplication, a great diversity from agro-morphological and biochemical point of view (Abdoli et al, 2009;Burba and Gomez Riera, 1997;Hong, 1999;Lallemand et al, 1997;Messiaen et al, 1993;Ovesna et al, 2007 andStavelìkova, 2008.). This variability is required; in fact, researchers benefit from the wide diversity of garlic for the selection of best genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely dispersed over the warm-temperate and temperate zones of the northern hemisphere. Today, it is grown in a number of countries and the leading producers are India, China and Korea [ 70 ]. It is rich in c-glutamylcysteine and other sulfur-containing compounds giving a characteristic flavor.…”
Section: Radioprotection By Medicinal Aromatic Plantsmentioning
confidence: 99%